2022
DOI: 10.1002/ird.2758
|View full text |Cite
|
Sign up to set email alerts
|

The use of mulch in cultivating the forage cactus optimizes yield in less time and increases the water use efficiency of the crop

Abstract: Measurements of crop evapotranspiration (ET C ) and crop coefficients (k C ) in cactus have not yet been adjusted for the phenological stage using conservation practices (i.e. mulching). In this study, soil water dynamics, ET C and k C were measured in the forage cactus under cultivation systems with (WM) and without (NM) the use of mulch in the semi-arid region of Brazil. Opuntia stricta was subjected to irrigation depths based on a percentage of the reference evapotranspiration (ET 0 ) (rainfed, 25, 50, 75 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
1
1
0
1
Order By: Relevance
“…The authors of [18], evaluating the controlled water deficit in forage cactus, found that greater soil water availability, even if in deficit for the crop, anticipates the harvest and optimizes the forage yield of these systems over time. This behavior was also observed by [14], where mulch was used on the soil, reducing water losses to the atmosphere, and thus increasing water use by the crop.…”
Section: Phenophases and Cutting Momentsupporting
confidence: 52%
See 1 more Smart Citation
“…The authors of [18], evaluating the controlled water deficit in forage cactus, found that greater soil water availability, even if in deficit for the crop, anticipates the harvest and optimizes the forage yield of these systems over time. This behavior was also observed by [14], where mulch was used on the soil, reducing water losses to the atmosphere, and thus increasing water use by the crop.…”
Section: Phenophases and Cutting Momentsupporting
confidence: 52%
“…In this context, forage cactus can be a strategic species to form resilient production systems, as it has the crassulacean acid metabolism (CAM) (e.g., stomatal opening at night and modified leaves), which provides a high capacity to withstand long periods of drought [12][13][14][15]. Furthermore, it has great potential as a source of bulk food for livestock, as the crop is an energy source for ruminants [16].…”
Section: Introductionmentioning
confidence: 99%
“…Unsur N merupakan unsur dengan pengaruh paling besar terhadap pertumbuhan dan metabolisme tanaman tipe Crassulacean Acid Metabolism /CAM (Pereira et al, 2019). Unsur N yang tersedia dalam kadar optimum akan meningkatkan aktivitas fotosintesis tanaman CAM (Alves et al, 2022;Sanchez-Mendoza et al, 2022). Gambar 7.…”
Section: Berat Segar Tajukunclassified